Selenosilane-Promoted Selective Mild Transformation of N-Thiophthalimides into Symmetric Disulfides - Viglianisi, Caterina; Bonardi, Chiara; Ermini, Elena; Capperucci, Antonella; Menichetti, Stefano; Tanini, Damiano (Synthesis, 2019)
The reactivity of N-thiophthalimides with silyl chalcogenides is described. Treatment of N-thiophthalimides with bis(trimethylsilyl) sulfide [(Me3Si)2S] leads to the formation of a mixture of the corresponding disulfides and trisulfides. On the other hand, N-thiophthalimides react with bis(trimethylsilyl) selenide [(Me3Si)2Se] under TBAF catalysis to smoothly give variously substituted diaryl, divinyl, and dialkyl disulfides; formation of a selenotrisulfide (dithiaselane, RSSeSR) is rationalized as an intermediate. Exploiting the different chemical behavior of silyl chalcogenides, we have disclosed a novel, selective, and operationally simple method to access disulfides in good yields under mild conditions.
Keywords: disulfides; selenosilane; N-thiophthalimides; trisulfides; selenium; sulfur